Pelatihan Eksplorasi Olah Vokal Teater di Sanggar Shedet Srepet Bojonegoro - Putri, Ratna Mestikasari; Pramono, Koko Hari; Lestari, Lilis (Sekolah Tinggi Kesenian Wilwatikta (STKW) Surabaya, 2025)
Exploration plays an important role in innovation and development of ideas or concepts in the field of art. By understanding new and complex phenomena of the need for innovation in an artistic process, art groups should be pioneers in developing exploration of traditional art-based works. This community service can develop new methods that are more efficient and in an effective focus of Vocal Theater Exploration Training at the Shedet Srepet Bojonegoro Studio. Exploration in the field of vocal training will make actors able to play ideal roles according to the needs of the character of the character being played. In the vocal exploration training activity at the Shedet Srepet Bojonegoro studio, the PKM team created a vocal creativity scheme in theater with a training method to improve the quality of vocal production for beginner actors. The selection of beginner actors is based on the needs of the studio to recruit regeneration and mentor new members to carry out performance productions on a staging work. Vocal training is considered one of the important elements that must be possessed by an actor, therefore vocal exploration is an important part to support studio activities in producing theater performances.